Tổ chức hành chính địa phương - Nguyễn, Hữu Tri (2011)
Tác giả: Nguyễn Hữu Tri, PGS-TS; Chu Xuân Khánh, ThS; Lê Thị Vân Hạnh, TS; Trần Ngọc Oanh, CN; Lê Văn Hòa, CN; Đỗ Thị Hải Ninh, CN; Nguyễn Thị Thu Vân, CN -- Từ khóa: Cơ quan hành chính; Tổ chức hành chính; Hành chính địa phương